A light-blocking greenhouse film differentially impacts climate control energy use and capsicum production - Lin, Terry; Maier, Chelsea R.; Liang, Weiguang; Klause, Norbert; He, Jing; Tissue, David T.; Lan, Yi-Chen; Sethuvenkatraman, Subbu; Goldsworthy, Mark; Chen, Zhong-Hua (Frontiers in Energy Research, 2024)
High-tech protected cropping holds great potential to improve global food security, but high cooling energy costs in warm climates pose difficulties in propagating the industry. Emerging technologies, such as diffuse glasses fitted with photoselective thin films, have interactions with crops and other cooling technologies which are not well-characterized for warm-climate glasshouses. A light-blocking film (LBF) was chosen as a high-tech, climate-controlled greenhouse cover permitting transmission of 85% of photosynthetically-active light and blocking heat-generating radiation. Two consecutive 7-month trials of two capsicum crops were grown under warm climate conditions partially impacted by bushfire smoke, with 2 cultivars (Gina and O06614) in the first trial, and 2 cultivars (Gina and Kathia) in the second trial. Capsicum fruit yield decreased by 3% in Gina and increased by 3% in O06614 for the first trial, and decreased by 13% in Gina, 26% in Kathia for the second trial. Cooling energy use increased by 11% and 12% for both capsicum crops in AE and SE respectively, with small but insignificant decreases in fertigation demand (2 – 5%). Cooling potential was significantly different from material specifications, with indications that convection from LBF interfaces was responsible for higher heat loads. LBF and similar absorptive glasses may still be beneficial for reducing nutrient, water, and energy use in warm climate glasshouses. However, yield is cultivar-dependent and may decrease with below-optimal crop lighting, whereas energy savings are more dependent on LBF orientation and building geometry than outside climate.